Quantity and location of aortic valve calcification predicts paravalvular leakage after transcatheter aortic valve replacement: a systematic review and meta-analysis - Shi, Jiale; Li, Wei; Zhang, Tangshan; Han, Chengwen; Wang, Zhengjun; Pei, Xinhao; Li, Xuetao; Zhao, Zidong; Wang, Pengbo; Han, Jingying; Chen, Shiqiao (Frontiers in Cardiovascular Medicine, 2023)
Introduction Transcatheter aortic valve replacement (TAVR) is the first-line treatment for patients with moderate-to-high surgical risk of severe aortic stenosis. Paravalvular leakage (PVL) is a serious complication of TAVR, and aortic valve calcification contributes to the occurrence of PVL. This study aimed to investigate the effect of location and quantity of calcification in the aortic valve complex (AVC) and left ventricular outflow tract (LVOT) on PVL after TAVR. Method We performed a systematic review and meta-analysis to evaluate the effect of quantity and location of aortic valve calcification on PVL after TAVR using observational studies from PubMed and EMBASE databases from inception to February 16, 2022. Results Twenty-four observational studies with 6,846 patients were included in the analysis. A high quantity of calcium was observed in 29.6% of the patients; they showed a higher risk of significant PVL. There was heterogeneity between studies (I2 = 15%). In the subgroup analysis, PVL after TAVR was associated with the quantity of aortic valve calcification, especially those located in the LVOT, valve leaflets, and the device landing zone. A high quantity of calcium was associated with PVL, regardless of expandable types or MDCT thresholds used. However, for valves with sealing skirt, the amount of calcium has no significant effect on the incidence of PVL. Conclusion Our study elucidated the effect of aortic valve calcification on PVL and showed that the quantity and location of aortic valve calcification can help predict PVL. Furthermore, our results provide a reference for the selection of MDCT thresholds before TAVR. We also showed that balloon-expandable valves may not be effective in patients with high calcification, and valves with sealing skirts instead of those without sealing skirts should be applied more to prevent PVL from happening. Systematic Review Registration https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=354630, identifier: CRD42022354630.